Evaluating municipal solid waste disposal options by AHP-based linguistic variable weight - Tarmudi, Zamali; Abdullah, Mohd Lazim; Md. Tap, Abu Osman (UTM, 2010)
The increase in municipal solid waste (MSW) being generated each year poses a serious dilemma in choosing the best MSW disposal system in Malaysia. Since the decision process involves uncertainty, multiple considerations, and incom- plete datasets, a simple and e±cient method is urgently required in order to achieve a better decision. This paper carried out the new approach in analytic hierarchy process which utilised the linguistic variables in order to derive the relative weights of each investigation attributes. The approach employs the natural expression judgment to quantify all the qualitative dataset related to MSW disposal problems in the studied areas. To demonstrate the feasibility of the proposed method, a case study in the state of Selangor and Kuala Lumpur Federal Territory was employed. It was found that the approach has great potential to deal with the uncertainty of datasets. Additionally, the approach is also very practical and user friendly since the decision makers can eas- ily evaluate the attributes using linguistic expressions fully. Finally, the method also considers the human rethinking-model in line with human nature that uses linguistic expressions to track subjectivity.